EIF4G1 gene mutations are not a common cause of Parkinson's disease in the Japanese population - Nishioka, Kenya; Funayama, Manabu; Vilariño-Güell, Carles; Ogaki, Kotaro; Li, Yuanzhe; Sasaki, Ryogen; Kokubo, Yasumasa; Kuzuhara, Shigeki; Kachergus, Jennifer M.; Cobb, Stephanie A.; Takahashi, Hirohide; Mizuno, Yoshikuni; et al. (Parkinsonism & related disorders, 2014)
Pathogenic mutations in the EIF4G1 gene were recently reported as a cause of autosomal dominant parkinsonism. To assess the frequency of EIF4G1 mutations in the Japanese population we sequenced the entire gene coding region (31 exons) in 95 patients with an apparent autosomal dominant inherited form of Parkinson's disease. We detected three novel point mutations located in a poly-glutamic acid repeat within exon 10. These variants were screened through 224 Parkinson's disease cases and 374 normal controls from the Japanese population. We detected the poly-glutamic acid deletion in exon 10 in two additional patients with sporadic Parkinson's disease. Although the EIF4G1 variants identified in the present study were not observed in control subjects, co-segregation analyses and population-based screening data suggest they are not pathogenic. In conclusion, we did not identify novel or previously reported pathogenic mutations (including the p.A502V and p.R1205H mutants) within EIF4G1 in the Japanese population, thus future studies are warranted to elucidate the role of this gene in Parkinson's disease.